A historical study of the Asian Men's Volleyball Championships from (1975) to (2021) - Omar Sabbar; Mohammed Ismail; Ali Jawad (College of Physical Education and Sport Sciences, 2024)
Studying the history of sports and knowing their achievements is of great importance as it is considered a means of advancement for societies and a measure of their culture and stages of development in all fields. One of the important sports games at the international and local levels is volleyball, which has a long history at the global level. The importance of the research lies in knowing the teams participating in the Asian championships and their most important results and where they were held from the first Asian Championship for men's teams in (1975) until the last championship held in Japan in (2021). Through the teams' participation in the Asian Men's Volleyball Championships, many teams have emerged on the Asian scene. The question here is whether there is documentation of these participations. What are the most important positions that the teams have obtained and also knowing the reasons for their development. And knowing the reasons for the fluctuations in the results and participations of some teams in the Asian Men's Championships. The most important conclusions reached by this research are that there are many achievements and participations for the teams that have not been documented. They have been documented.